Ramanujan through a Biopic - NIKALJE, VARADA (THE PRIMARY TEACHER, 2016)
Say the words ‘mathematical genius’ and the image that comes to the mind is that of a person scribbling apparently meaningless but complex mathematical calculations all over a blackboard. Such images reinforce the idea that mathematics involves long calculations, and that it is too complex for ordinary mortals, and that it is an abstract discipline not connected with practical life — all of which are untrue. As a well-known mathematics professor puts it, “The hope of improvement in mathematics teaching, whether in schools or in colleges, lies mainly in the possibility of humanising it. It is worthwhile to remember that our pupils are human beings...to humanise the teaching of mathematics means to present the subject, so as to interpret its ideas and doctrines, that they should appeal, not merely to the logical faculty, but to the power of interest of the human mind”. (Keynes, 1912).